2007
DOI: 10.1111/j.1365-2621.2006.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial activity of Indian spices against common foodborne pathogens

Abstract: The present study was designed to evaluate the antimicrobial activity of six Indian spice extracts, namely clove, cinnamon, mustard, garlic, ginger and mint. All of these have been traditionally used in folk medicine, and are still used in the alternative system of health care. The antimicrobial activity of these commonly used Indian spices was tested against three potent foodborne pathogens, namely Escherichia coli,Staphylococcus aureus and Bacillus cereus, which are responsible for many health-related proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 33 publications
3
48
2
1
Order By: Relevance
“…Previous studies showed the similar results up to some extent (Ahmad and Beg, 2001;Arora and Kaur, 1999;Sofia et al, 2007;Shan et al, 2007;Sunilson et al, 2009;Weerakkody et al, 2010;Negi, 2012). In literature, various studies have been published on the antimicrobial activities of plant extracts against different microorganisms.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies showed the similar results up to some extent (Ahmad and Beg, 2001;Arora and Kaur, 1999;Sofia et al, 2007;Shan et al, 2007;Sunilson et al, 2009;Weerakkody et al, 2010;Negi, 2012). In literature, various studies have been published on the antimicrobial activities of plant extracts against different microorganisms.…”
Section: Discussionsupporting
confidence: 62%
“…A variety of plant and spice based antimicrobials is used for reducing or eliminating pathogenic microorganisms and increase the shelf life of food (Tajkarimi et al, 2010). In India, natural herbs and spices are consumed either in food or used as medicine in order to maintain proper sanitation, health and hygiene and to increase longevity of life (Sofia et al, 2007). Several spices such as ajowan, clove, ginger, black pepper, cumin and asafetida are commonly used in the Indian diet (Arora and Kaur, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the findings of some previous studies (Silva et al 2011;Sofia et al 2007), in this study, it has been observed that the two spice extracts, namely C. sativum and B. nigra, had no antimicrobial effect against test pathogens. Nonetheless, they might still be useful as flavor enhancers, anti-oxidant and coloring agents.…”
Section: Resultscontrasting
confidence: 56%
“…In case of C samples, there was a steady increase in all the counts and the sample was completely spoiled (putrid) by 2nd day. The inhibitory effect of clove extract E. coli, S. aureus, B. cereus and spoilage organisms has been well established (Karur Sofia et al 2007, Baohua Kong et al 2007) and on certain fungi (Omidbeygi et al 2007;Tullio et al 2007;Guo and Cheng 2006;Viuda Martos et al 2007). Present investigation revealed the inhibitory effect of clove extract on meat spoilage organisms, the effect being more profound because of the low surface pH of mutton caused by acidulant treatment (Sara Burt 2004).…”
Section: Resultsmentioning
confidence: 99%